Investigating Malaysia university student’s online purchase intention towards Korean cosmetic products in Klang valley - Choong, Yi Han; Teh, Evangeline Luo Ru (2019)
This research intends to determine factors that influence university students’ online purchase intention towards Korean cosmetic products in online stores. Survey questionnaires were adapted to collect data and 300 copies of questionnaires have been distributed online to 300 respondents within Klang Valley area in Malaysia with the used of the convenience sampling method. Data analysis was done with the help of the Statistical Package for Social Science (SPSS) software. Result obtained shows that social influence and performance expectancy have a significant relationship with online purchase intention. However, trust, perceived price and effort expectancy has no impact on online purchase intention. In addition, managerial implications have been discussed to help marketers and online retailers to have a better understanding on factors that affecting Malaysian university students’ online purchase intention towards Korean cosmetics. Lastly, limitations and recommendations for future study have been discussed so that future researchers can improve the quality of their research in related fields.